Ocena działalności władz samorządowych w zakresie wspierania rozwoju lokalnej przedsiębiorczości - Angowski, Marek (Evaluation of Local Government Activity in Supporting Local Entrepreneurship Development, 2008)
The development of local entrepreneurship, especially SME sector, is very important in the period of structural changes and adopting processes of the Polish economy to the effective competition in the EU market. There is a need for creating development supporting system for small and medium enterprises. It is an active role of local governments to create and promote this sector. The paper presents the results of research on SME's business activity in Lublin region. The research concerns the role and influence of local governments in creating small and medium entrepreneurship. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 364-373